Pengaruh Kedisiplinan dan Task Commitment terhadap Prestasi Belajar Matematika - Anies Pianyta (Universitas Indraprasta PGRI, 2016)
This corrasional survey research with double regression analysis is aimed at 1) acknowledging the impacts of both discipline and task commitment on mathematical learning achievement all together 2) acknowledging the impacts of discipline on mathematical learning achievement 3) acknowledging the impact of task commitment on mathematical learning achievement. The benefits of this research is to add knowledge and increase the quality of national education. This research was conducted at SMP PGRI Plumbon, Cirebon District in 2015/2016 by using simple random sampling with 56 respondents taken from the number of affordable population reach as many as 65 respondents. The instrument used is test on variables of mathematical learning achievement and questionnaire on variables of discipline and task commitment and all instruments have been empirically validated. Hypothesis is conducted after the data fulfill in series of classic assumption test, i.e. normality test, linearity test and multicollinearity test. Hypothesis test with Ftest and test. The research result show that 1) there are significant impacts of both discipline and task commitment on mathematical learning achievement all together about 37,3% 2) there are significant impacts of disciple on mathematical learning achievement about 20,8 %; 3) there are significant impacts of task commitment on mathematical learning achievement about 16,5%.